A Phenomenological Study of Nurse Manager Interventions Related to Workplace Bullying. (October 2015) - Skarbek, Anita J.; Johnson, Sandra; Dawson, Christina M.
Abstract : Objective: The aim of this study was to acquire nurse managers' perspectives as to the scope of workplace bullying, which interventions were deemed as effective and ineffective, and what environmental characteristics cultivated a healthy, caring work environment. Background: Research has linked workplace bullying among RNs to medical errors, unsafe hospital environments, and negative patient outcomes. Limited research had been conducted with nurse managers to discern their perspectives. Methods: Six nurse managers from hospital settings participated in in-depth, semistructured interviews. Ray's theory of bureaucratic caring guided the study. Results: These themes emerged: ( a ) awareness, ( b ) scope of the problem, ( c ) quality of performance, and ( d ) healthy, caring environment. Findings indicated mandated antibullying programs were not as effective as individual manager interventions. Conclusions: Systems must be in place to hold individuals accountable for their behavior. Communication, collective support, and teamwork are essential to create environments that lead to the delivery of safe, optimum patient care.